2017
DOI: 10.1093/nar/gkx764
|View full text |Cite
|
Sign up to set email alerts
|

The RNA chaperone La promotes pre-tRNA maturation via indiscriminate binding of both native and misfolded targets

Abstract: Non-coding RNAs have critical roles in biological processes, and RNA chaperones can promote their folding into the native shape required for their function. La proteins are a class of highly abundant RNA chaperones that contact pre-tRNAs and other RNA polymerase III transcripts via their common UUU-3′OH ends, as well as through less specific contacts associated with RNA chaperone activity. However, whether La proteins preferentially bind misfolded pre-tRNAs or instead engage all pre-tRNA substrates irrespectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 60 publications
(144 reference statements)
4
31
0
Order By: Relevance
“…The m2,2G modification has been predicted to prevent the folding of certain nuclearencoded tRNAs into alternative conformers found in mitochondrial tRNAs (Steinberg and Cedergren 1995). Moreover, previous studies in S. cerevisiae have found that certain tRNA isoacceptors exhibit decreased accumulation in the absence of Trm1, suggesting that the m2,2G modification plays a role in the proper folding of certain tRNAs (Dewe et al 2012;Vakiloroayaei et al 2017). Interestingly, we have found that TRMT1-deficient human cells exhibit similar steadystate levels of all tested nuclear-and mitochondrial-encoded tRNAs (Dewe et al 2017).…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…The m2,2G modification has been predicted to prevent the folding of certain nuclearencoded tRNAs into alternative conformers found in mitochondrial tRNAs (Steinberg and Cedergren 1995). Moreover, previous studies in S. cerevisiae have found that certain tRNA isoacceptors exhibit decreased accumulation in the absence of Trm1, suggesting that the m2,2G modification plays a role in the proper folding of certain tRNAs (Dewe et al 2012;Vakiloroayaei et al 2017). Interestingly, we have found that TRMT1-deficient human cells exhibit similar steadystate levels of all tested nuclear-and mitochondrial-encoded tRNAs (Dewe et al 2017).…”
Section: Discussionsupporting
confidence: 59%
“…While S. cerevisiae strains lacking Trm1 are viable, Trm1-null strains display temperature sensitivity and defects in tRNA stability that are further exacerbated by combined deletion of either the Trm4p tRNA methyltransferase or the La RNA binding protein (Copela et al 2006;Dewe et al 2012). Furthermore, studies in Schizosaccahromyces pombe have identified particular tRNAs that are dependent upon Trm1p and/or La for proper folding, aminoacylation and accumulation (Vakiloroayaei et al 2017). These observations highlight a key role for Trm1p-catalyzed m2,2G modifications in the stabilization of tRNA structure and function.…”
Section: Introductionmentioning
confidence: 95%
“…Moreover, previous studies in S. cerevisiae have found that certain tRNA isoacceptors exhibit decreased accumulation in the absence of Trm1, suggesting that the m2,2G modification plays a role in the proper folding of certain tRNAs (Dewe, Whipple, Chernyakov, Jaramillo, & Phizicky, 2012;Vakiloroayaei, Shah, Oeffinger, & Bayfield, 2017). Interestingly, we have found that TRMT1-deficient ZHANG ET AL.…”
mentioning
confidence: 47%
“…The m2,2G modification has been predicted to prevent the folding of certain nuclear‐encoded tRNAs into alternative conformers found in mitochondrial tRNAs (Steinberg & Cedergren, 1995). Moreover, previous studies in S. cerevisiae have found that certain tRNA isoacceptors exhibit decreased accumulation in the absence of Trm1, suggesting that the m2,2G modification plays a role in the proper folding of certain tRNAs (Dewe, Whipple, Chernyakov, Jaramillo, & Phizicky, 2012; Vakiloroayaei, Shah, Oeffinger, & Bayfield, 2017). Interestingly, we have found that TRMT1‐deficient human cells exhibit similar steady‐state levels of all tested nuclear‐ and mitochondrial‐encoded tRNAs (Dewe et al, 2017).…”
mentioning
confidence: 93%
“…Often, these UUU-3’OH independent binding modes have been implicated in La function as an RNA chaperone. RNA chaperone activity in human La has been mapped to the RRM1 as well as the disordered CTD ( 17 , 20 ), and it has been proposed that one of the functions of the UUU-3’OH depending binding mode is to recruit non-specific La-associated RNA chaperone activity to UUU-3’OH containing substrates ( 21 ). It is thus hypothesized that binding of La to RNA targets in vivo occurs through the co-operation of a number of RNA binding modes in combination ( 15 , 22 ), and that the specificity determinants for some of these binding modes are still nebulous.…”
Section: Introductionmentioning
confidence: 99%